2018
DOI: 10.1007/s00210-018-1589-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of spatial learning and memory in the Barnes maze task in rodents—methodological consideration

Abstract: Among the methods valuable for assessing spatial learning and memory impairments in rodents, the Barnes maze (BM) task deserves special attention. It is based on the assumption that the animal placed into the aversive environment should learn and remember the location of an escape box located below the surface of the platform. Different phases of the task allow to measure spatial learning, memory retrieval, and cognitive flexibility. Herein, we summarize current knowledge about the BM procedure, its variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
149
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(185 citation statements)
references
References 106 publications
(296 reference statements)
10
149
0
2
Order By: Relevance
“…In the first probe trial, we observed significant differences in escape latency between pristane/pristane+LPS vs. control group at 7wLPS in STM D3-D4, and were maintained in LTM probe. The subgroup of control mice decrease in escape latency as expected, as consequence of memory consolidation and learning process observed in other studies[27]. Nevertheless, mice treated with pristane and pristane+LPS showed an erratic behavior and anxiety, that resulted in a prolongated time to reach and enter in to escape hole.…”
Section: Discussionsupporting
confidence: 82%
“…In the first probe trial, we observed significant differences in escape latency between pristane/pristane+LPS vs. control group at 7wLPS in STM D3-D4, and were maintained in LTM probe. The subgroup of control mice decrease in escape latency as expected, as consequence of memory consolidation and learning process observed in other studies[27]. Nevertheless, mice treated with pristane and pristane+LPS showed an erratic behavior and anxiety, that resulted in a prolongated time to reach and enter in to escape hole.…”
Section: Discussionsupporting
confidence: 82%
“…S4 ). Similarly, the Barnes Maze relies on accurate tracking to test how fast an animal acquires a spatial memory by finding an escape tunnel or a food reward in one of many holes placed around a circular platform [ 41 ]. Our approach precisely tracks the movement of a mouse across the maze, and records the time it spends investigating different holes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In case of animal model, the TLE was evaluated by the Racine scores, lesser the scores better the potency of the drug. The cognitive functions were assessed by BM [17,24]. Escape latency and error score were assessed in BM, as shown in Figs.…”
Section: Discussionmentioning
confidence: 99%